Frequency and Correlates of Online Consultations With Doctors or Therapists in Middle-Aged and Older Adults: Nationally Representative Cross-sectional Study - André Hajek; Hans-Helmut König (JMIR Publications, 2022)
BackgroundA few studies have identified the frequency and correlates of online consultations with doctors or therapists. However, there is a lack of studies using nationally representative data from middle-aged and older adults in Germany. ObjectiveThis study aims to determine the frequency and correlates of online consultations with doctors or therapists in Germany. MethodsFor this study, cross-sectional data were taken from the nationally representative German Ageing Survey (DEAS; n=3067 in the analytical sample; age range 46-98 years). As part of the DEAS, a short survey was conducted between June 8 and July 22, 2020, examining the everyday life and living conditions among these middle-aged and older individuals during the COVID-19 pandemic. The frequency of online consultations with doctors or therapists served as the dependent variable (daily, several times a week, once a week, 1-3 times a month, less often, and never). Multiple logistic regressions were performed. ResultsIn sum, 10.02% (381/3806) of individuals with access to the internet had online consultations with doctors or therapists. Multiple logistic regressions showed that the likelihood of using online consultations with doctors or therapists (compared with those never using such services) was positively associated with higher education (compared with medium education; odds ratio [OR] 1.31, 95% CI 1.01-1.70), living with a partner in the same household (compared with single; OR 1.53, 95% CI 1.05-2.22), poorer self-rated health (OR 1.42, 95% CI 1.16-1.74), increased loneliness (OR 1.45, 95% CI 1.10-1.90), and increased satisfaction with life (OR 1.30, 95% CI 1.03-1.64). ConclusionsStudy findings suggest that a non-negligible proportion of about 1 out of 10 individuals aged 46 years and over had online consultations with doctors or therapists. However, compared with other countries, this proportion remains small. Knowledge about the correlates of (non)use may assist in identifying corresponding individuals. In times of reshaping the health care system, these efforts in online consultations with doctors or therapists may contribute to addressing patient needs. Moreover, increased use of such services may reduce the risk of getting infected with SARS-CoV-2 by reducing social contact.